Wykorzystanie analizy dyskryminacyjnej z autokorelacją przestrzenną do klasyfikacji obiektów - Batóg, Jacek (The Application of the Discriminant Analysis with the Spatial Autocorrelation to the Classification of Objects, 2009)
The aim of the paper is the presentation of the modification of the classical discriminant analysis. This proposal is connected with the occurrence of the spatial autocorrelation. The spatial autocorrelation is described by matrix of spatial weights. Its elements represent directly nonmeasurable spatial relations between discriminated objects. This approach is an alternative solution to existing methods based on correcting of a priori or a posteriori probabilities. The empirical verification of the proposed method testifies the significant improvement of the accuracy of the classification when the spatial discriminant analysis is applied. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 382-389